Appearance of lipid floating and tear film stability in non-dry and dry eye subjects - Ithnin, Mohd. Hafidz; Ariffin, Azrin Esmady; Mohd Kamal, Khairidzan (Faculty of Medicine, University of Malaya, 2017)
Introduction: Assessment of lipid component of the tear film is still poorly described. The purpose of the study is to evaluate the appearance of lipid floating and tear film stability in non-dry and dry eye subjects.